Grafted monolayers of the neutral Cu(ii) complex of a dioxo-2, 3, 2 ligand: surfaces with decreased antibacterial action. (1st March 2018) - Taglietti, A.; Grisoli, P.; Dacarro, G.; Gattesco, A.; Mangano, C.; Pallavicini, P.
Abstract : A monolayer of the neutral Cu 2+ complex of a silane-bearing diamino–diamido ligand is formed on glass, exhibiting (decreased) antibacterial properties. Abstract : Monolayers of the Cu 2+ complex of a diamino–diamido ligand can be grafted on plain glass obtaining the pH-controlled release of the Cu 2+ cation for antibacterial surfaces whose microbicidal effect is lowered by the neutral charge of the complex.